Mobility support in Wireless Sensor Network in Healthcare-A Survey - Narang, Ritika; Malik, Amita (International Journal of Computer Sciences and Engineering, 2025)
Mobility in healthcare helps to promote clinical collaboration. By providing timely access to Patient Health Information, it helps doctors to take critical care decisions. Mobility in healthcare is enhancing the accessibility of critical firm and clinical systems. These days, condition devices are advancing closer to patient’s point-of-care. Network based mobility protocols are suitable for 6LoWPAN because in these protocols network initiates the message signaling and reduces the load on low power sensor nodes by relieving them from participating in mobility procedure, result in enhancing lifetime of network. Proxy Mobile IPv6 (PMIPv6) is suitable mobility solution as it is Network based mobility protocol alongside it provides single hop communication but single hop communication is not sufficient for LoWPAN. Sensor Proxy Mobile IPv6 (SPMIPv6) is an optimization of PMIPv6 and appropriate for low power sensor nodes as it reduces message signaling overload ,optimize power consumption and minimize mobility cost compare to PMIPv6 and MIPv6.